IMPLIKASI SISTEM KEKERABATAN PATRILINEAL TERHADAP KEWARISAN ANAK PEREMPUAN DALAM SUKU ADAT ALAS (Studi Kasus di Kabupaten Aceh Tenggara) - Amsanul Amri; Muhammad Nasir (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
The problem of inheritance in society is a social phenomenon that isdirectly related to legal issues. Inheritance in the legal perspective regulates thetransition of property left by a deceased person to his heirs under terms andconditions stipulated under Islamic law, positive law, and customary law thatgrows and develops within a society. With regard to the customary law system ofAlas, the implementation of inheritance in Southeast Aceh Regency there is aregulatory gap between Islamic law and the positive law prevailing in Indonesiawith customary law prevailing in Southeast Aceh Regency, especially regardingthe position of the heir of girls. Theoretically, the kinship system adopted in Alassociety is a patrilineal pattern that draws the lineage from the fathers. This systemin practice has implications for the inheritance of girls who do not seem to havethe right to inheritance. All high-value inheritance collectively is controlled bymale heirs, such as fathers, sons, uncles, grandfathers, even adopted sons can alsohinder the inheritance of girls.